2016
DOI: 10.1093/mnras/stw2570
|View full text |Cite
|
Sign up to set email alerts
|

Optical, UV, and X-ray evidence for a 7-yr stellar cycle in Proxima Centauri

Abstract: Stars of stellar type later than about M3.5 are believed to be fully convective and therefore unable to support magnetic dynamos like the one that produces the 11-year solar cycle. Because of their intrinsic faintness, very few late M stars have undergone long-term monitoring to test this prediction, which is critical to our understanding of magnetic field generation in such stars. Magnetic activity is also of interest as the driver of UV and X ray radiation, as well as energetic particles and stellar winds, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
103
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 78 publications
14
103
2
1
Order By: Relevance
“…The true Alfvén surface will be fairly dynamic and depend on the exact wind conditions at any given time. The strong dependence of the Alfvén surface size on the magnetic field strength and the likely variation of this, together with the recently detected magnetic cycles (Wargelin et al 2016), suggest Proxima b is likely to encounter transitions between subsonic and supersonic wind conditions quite frequently. Cohen et al (2014) found that the lack of a bow shock in subsonic conditions leads to much deeper penetration of the wind into the magnetosphere than in supersonic conditions.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The true Alfvén surface will be fairly dynamic and depend on the exact wind conditions at any given time. The strong dependence of the Alfvén surface size on the magnetic field strength and the likely variation of this, together with the recently detected magnetic cycles (Wargelin et al 2016), suggest Proxima b is likely to encounter transitions between subsonic and supersonic wind conditions quite frequently. Cohen et al (2014) found that the lack of a bow shock in subsonic conditions leads to much deeper penetration of the wind into the magnetosphere than in supersonic conditions.…”
Section: Resultsmentioning
confidence: 86%
“…Magnetic field strength scales with rotation period, and to account for this we have scaled the magnetic map to match the field strength measured for Proxima of ∼600 G (Reiners & Basri 2008). Since this is only a single measurement of the average magnetic field strength and magnetic cycles have been detected on Proxima (Wargelin et al 2016), we probe two different scalings. In one, the amplitude (or maximum strength) of the magnetic field is 600 G (see Figure 1) and in the other the mean magnetic field is 600 G and the maximum value is 1200 G (and looks exactly like the magnetogram in Figure 1 but with a color bar going up to 1200 G).…”
Section: Magnetohydrodynamic Modelingmentioning
confidence: 99%
“…An earlier reporting (Cincunegui et al 2007) suggested an activity cycle length of about 1.2 years. Recent work based on a longer data set could not confirm the 1.2 year period but found strong evidence for cycles with a length of approximately 7 years (Mascareño et al 2016;Wargelin et al 2017).…”
Section: Introductionmentioning
confidence: 89%
“…This would explain the difference in magnetic fields between individual objects. Note that the signs of activity cycles were found in some M dwarfs stars based on photometric/spectroscopic observations 27 , including a recent detection of a clear 7 year photometric cycle in fully convective and slowly rotating (P ≈ 83d) M dwarf Proxima Centauri 28 . By computing a model for this star it was shown that dynamo in fully convective M dwarfs can indeed generate magnetic cycles with repeated reversals of the magnetic polarities at different latitudes with time, provided that these stars rotate slow enough to develop differential rotation in their convection zones 29 .…”
mentioning
confidence: 84%